2019
DOI: 10.1088/2058-6272/aafc50
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gas flow pattern on the generation of ozone in surface dielectric barrier discharge

Abstract: Ozone production utilizing surface dielectric barrier discharge (SDBD) was experimental studied for different flow patterns considering the influences of transversal flow, lateral flow and different lateral flow positions. Results show that the flow patterns have a remarkable impact on the ozone yield by affecting the uniformity and turbulence of gas flow. Meanwhile, distributing the O 2 flow rate according to the intensity of the plasma reaction would also increase the generation efficiency of SDBD for ozone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Many authors [35][36][37][38][39] have calculated the total power in the discharge by integrating the product i(t)u(t) as described in equation (2), where i(t) was measured directly by Pearson current probe which, in single-shot, results in similar I -V curves (also shown in figures 4(a) and (b)).…”
Section: Electrical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors [35][36][37][38][39] have calculated the total power in the discharge by integrating the product i(t)u(t) as described in equation (2), where i(t) was measured directly by Pearson current probe which, in single-shot, results in similar I -V curves (also shown in figures 4(a) and (b)).…”
Section: Electrical Characteristicsmentioning
confidence: 99%
“…Xie et al [39] reported a BPY of 131 g (kW h) −1 using surface DBD in oxygen. This was established at an oxygen flow of 0.9 slm, SIE 30 J L −1 (figure 10b [39]) and a concentration 6 g m −3 (approx 2800 ppm).…”
Section: Comparison Of Msdbd With Other Dbd Geometriesmentioning
confidence: 99%
“…Different experimental techniques may be implemented for plasma production, but a DBD [11][12][13][14], powered by alternating current sources, is of special interest for these applications due to relative simplicity of its technical realization and the ability to be easily integrated into various gas flow configurations with a large cross section [15,16]. The most common application of a DBD is ozone production [17,18]. DBD was also studied for plasma assisted combustion [19], and a radio frequency DBD-even for singlet oxygen [20] and iodine atoms [21] production for oxygeniodine laser.…”
Section: Introductionmentioning
confidence: 99%
“…In the surface discharge case, there is at least one path along which the two electrodes may be reached through the dielectric barrier only. This concept attracts interest for a large variety of fields, including medicine [17][18][19][20][21], material processing [22][23][24], flow field control (plasma actuators) [25][26][27], aerodynamic propulsion [28][29][30][31], assisted combustion [32][33][34][35], icing control [36][37][38], ozone generation [39][40][41][42], environment [43][44][45], and agriculture [46,47], just to name a few.…”
Section: Introductionmentioning
confidence: 99%